Penerapan Media Kertas Kokoru untuk Meninggkatkan Motorik Halus Anak Usia Dini - Mufidah Putri Amana; Verawati Usman; Nazwa Muhamad; Pupung Puspa Ardini; Mutmaina Djafar; Apriliandi Koungo; Nazwa Varawansa Latif (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Fine motor skills are one of the essential aspects of early childhood development, involving the ability to use small muscles, particularly in hand–eye coordination. However, some children still experience difficulties in activities such as cutting, pasting, and arranging shapes due to the limited availability of engaging and varied learning media. This study aims to describe the implementation of kokoru paper as a learning medium to improve children's fine motor skills through letter-matching activities and arranging paper pieces around a sun-shaped pattern. This study employed a descriptive qualitative approach involving children aged 4–5 years as the research subjects. Data were collected through observation, interviews, and documentation. The findings indicate that the use of kokoru paper effectively enhances children's fine motor skills, particularly in cutting, pasting, arranging shapes, and improving hand–eye coordination. In addition, children were more active, focused, and enthusiastic throughout the learning activities. Besides improving fine motor skills, the activities also helped children recognize letters and develop their creativity. Therefore, kokoru paper can serve as an effective and enjoyable alternative learning medium for enhancing fine motor skills in early childhood.